KOMPRES AIR HANGAT DAN NYERI PERSALINAN - Nur Anita; Raehan; Sarini Ganing (Bina Generasi : Jurnal Kesehatan, 2023)
Labor pain is a physiological condition, pain comes from uterine contraction and cervical dilation. Labor pain can affect the mother’s condition in the form of fatigue fear, worry and stress, stress can cause weakening of unterine contractions and result in prolongen labor.Giving warm water compresses is one method to reduce labor pain in maternity mothers. The purpose of the preparation of this final project is to find out whether there is an effect of using warm water compresses in reducing labor pain in mothers during the active phase of labor at the Banggae 1 Majene public health center. This type of research uses a quasi experimental, and the desaign used in the study in two different groups, namely the control group and the experimental group. Whit the aim of knowing the scale of labor pain and the effect of using warm water compresses on mothers during the active phase of labor at the Banggae 1 Majene public health center, using an observation sheet pn primary data taken directly from respondents, with a total sample of 30 respondents, namely 15 as the control group, and 15 as the experimental group. Based on the results of this study, the respondent’s labor pain scale without being given warm water compresses, namely severe pain as many as 11 people (73,3%) and very severe pain as many as 4 people (26,6%). While the labor pain scale of respondents who were given warm water compresses, namely moderate pain as many as 13 people (86,6%) and severe pain as many as 2 people (13,3%). Conclusions from the effect of using warm water compresses on reducing labor pain in mothers during the active phase of labor at the Banggae 1 Majene public health center. There is an effect of giving warm water compresses to reducing labor pain with the results of hypothesis testing H0 being rejected and H1 being accepted with a significant value of 0,00<0,05. So warm water compresses have an effect on reducing labor pain during the active phase at the Banggae 1 Majene health center 2022.